(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In the context of global globalization, the electoral system plays an invaluable role in strengthening democracy. Elections are democratic if they are fair, transparent, and comply with universal electoral standards. In modern societies, the concepts of democracy and elections are closely related. The participation of the people in the formation of state governance is carried out through elections, that is, democratic elections. In Central Asia, and in particular, in Uzbekistan, many reforms have been implemented in recent years to further democratize the electoral system and increase citizen participation and activity in elections. The reforms to improve the electoral system must include increasing the influence of political parties in the society.